2018
DOI: 10.26493/1854-4231.13.213-225
|View full text |Cite
|
Sign up to set email alerts
|

Could the Suitability of the Existing Accounting System be Argued

Abstract: Accounting is a process of recording and studying financial data related to company's operations. Its aims are above all to provide information about the events in company business life in an agreed language comprehensible to accounting information users and to provide information which is vital to business decisionmaking. If we consider the above mentioned aims, we can establish that it is not easy to reach them. Accounting is not an exact science, which means that approximations or planned amounts are very o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ordia and Bhanawat (2017) found that Indian companies' consistency in EVA and EVA-related financial parameters are observed after adopting IFRS. Milost and Cepar (2018) pointed out that classical accounting considers various elements of the business process in a different way, which means it is inconsistent. Relevant empirical research has proved that international convergence of accounting standards can enhance the comparability of a country's accounting information (DeFond et al, 2011;Yip and Young, 2012;Barth et al, 2012).…”
Section: Ownership Concentration and Consistencymentioning
confidence: 99%
“…Ordia and Bhanawat (2017) found that Indian companies' consistency in EVA and EVA-related financial parameters are observed after adopting IFRS. Milost and Cepar (2018) pointed out that classical accounting considers various elements of the business process in a different way, which means it is inconsistent. Relevant empirical research has proved that international convergence of accounting standards can enhance the comparability of a country's accounting information (DeFond et al, 2011;Yip and Young, 2012;Barth et al, 2012).…”
Section: Ownership Concentration and Consistencymentioning
confidence: 99%